Theory of mind and its relationship with executive functions and emotion recognition in borderline personality disorder - Báez Buitrago, Sandra Jimena (2015)
Impaired social cognition has been claimed to be a mechanism underlying the development and maintenance of borderline personality disorder (BPD). One important aspect of social cognition is the theory of mind (ToM), a complex skill that seems to be influenced by more basic processes, such as executive functions (EF) and emotion recognition. Previous ToM studies in BPD have yielded inconsistent results. This study assessed the performance of BPD adults on ToM, emotion recognition, and EF tasks. We also examined whether EF and emotion recognition could predict the performance on ToM tasks. We evaluated 15 adults with BPD and 15 matched healthy controls using different tasks of EF, emotion recognition, and ToM. The results showed that BPD adults exhibited deficits in the three domains, which seem to be task-dependent. Furthermore, we found that EF and emotion recognition predicted the performance on ToM. Our results suggest that tasks that involve real-life social scenarios and contextual cues are more sensitive to detect ToM and emotion recognition deficits in BPD individuals. Our findings also indicate that (a) ToM variability in BPD is partially explained by individual differences on EF and emotion recognition; and (b) ToM deficits of BPD patients are partially explained by the capacity to integrate cues from face, prosody, gesture, and social context to identify the emotions and others' beliefs.